THE PERCEPTION OF FOREIGN LANGUAGE CENTRE (FLC) STUDENTS TOWARDS IDIOMATIC SPEAKING CLASS - Lasmini; Laila Wati; Siti Maysuroh; M. Adib Nazri (Jurnal Intelek Insan Cendikia, 2024)
The research investigates the impact of an idiomatic speaking class on students' English-speaking skills and their perceptions of the learning experience. The research, conducted at the Foreign Language Center in Selong, East Lombok Regency, used qualitative methods like observations, questionnaires, and interviews. The findings showed that 68.75% of students enjoyed learning idioms and found the class beneficial. Despite considering idioms challenging, students appreciated the interactive teaching methods, which included games and discussions, for making the learning process engaging and effective. Although students faced difficulties with pronunciation and memorization of idioms, the supportive teaching methods and tutor feedback were instrumental in overcoming these challenges. The class also contributed to increased confidence and proficiency in speaking, with students noting significant improvements in their ability to use idiomatic expressions in conversation. In conclusion, the idiomatic speaking class was found to be a valuable component of English language education, significantly enhancing students' speaking skills and boosting their motivation and confidence in using idiomatic expressions. The study highlights the importance of interactive teaching methods and supportive learning environments in overcoming challenges and improving language proficiency.